Mechanical behavior and corrosion properties of Ti-7Mo-8Nb alloy for biomedical applications - Modar Saood; Khaled M Ibrahim; Emad El-kashif; Madiha Shoeib; Abobakr Elshalakany; Mamdouh S Mohamed (Materials Research Express, 2021)
The present study investigates the microstructural, mechanical and corrosion properties of Ti-7Mo-8Nb alloy manufactured through powder metallurgy. The performance of the developed alloy is benchmarked against cast Ti-6Al-4V. Microstructure examination of Ti-7Mo-8Nb revealed a Widmanstätten structure containing equiaxed β grains along with acicular α phase. In regards to the mechanical properties, Ti-7Mo-8Nb possessed higher compressive yield strength, higher hardness but lower elastic modulus than Ti-6Al-4V. The elastic modulus of Ti-7Mo-8Nb was almost 44.9 GPa, approaching the usually desired value of 30 GPa for cortical bone. Wear test revealed also a lower wear rate for Ti-7Mo-8Nb. Potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) experiments were carried out for both Ti-7Mo-8Nb and Ti-6Al-4V immersed in Hank’s solution as a simulated body fluid at a temperature of 37 °C. Both experiments revealed higher corrosion resistance for Ti-7Mo-8Nb manifested by lower corrosion and passivation current densities, higher negative phase angle, higher impedance modulus and larger Nyquist semicircle diameter as compared to Ti-6Al-4V alloy. The superior corrosion properties of Ti-7Mo-8Nb are indicative of the development of a more stable passive layer on the surface. The fitting of EIS data into an equivalent circuit suggested the formation of a double oxide layer consisting of an inner compact base passive film along with an external porous layer. The presented combination of high strength, high corrosion resistance along with low elastic modulus puts forward the Ti-7Mo-8Nb alloy as a good candidate for orthopedic biomedical applications.